PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUICK ON THE DRAW UNTUK MENINGKATKAT HASIL BELAJAR SISWA PADA POKOK BAHASAN STOIKIOMETRI DI KELAS X SMA NEGERI 5 PEKANBARU - Velly Noverina; Islamias Islamias; Rini Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack: Research on the application of cooperative learning model Quick On The Draw has been conducted to improve student learning achievement on the topic stoichiometry at class X SMAN 5 Pekanbaru. This research is experimental research with randomized control group pretest-posttest design. The sample took in the 9 January – 20 February 2013. The sample consisted of two classes, X3 class as experimental class and X2 class as control class. Experimental Class is the class with cooperative learning model Quick On The Draw and Control Class is the class with no cooperative learning model Quick On The Draw. Analyze of data by used t-test formula. Result of data processing obtained tcount>ttable is 2,416 > 1,67. It means that the application of cooperative learning model Quick On The Draw can improve student achievement on the topic stoichiometry at class X SMAN 5 Pekanbaru.Keyword: cooperative learning, quick on the draw, study achievement,stoichiometry